Post-surgical enterocutaneous fistulas, risk factors and complications in the Guayaquil hospital. January 2010 to December 2014. (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
The worldwide prevalence of this pathology varies from
Keywords: fistulas; complications; risk factors